2006
DOI: 10.1002/asia.200600371
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Crossover Physical Gels: A Quick Thermoreversible Response Assisted by Dynamic Self‐Organization

Abstract: Iron(II) triazolate coordination polymers with lipophilic sulfonate counterions with alkyl chains of different lengths have been synthesized. In hydrocarbon solvents, these polymers formed a physical gel and showed a thermoreversible spin transition upon the sol-gel phase transition. The formation of a hydrogen-bonding network between the triazolate moieties and sulfonate ions, bridged by water molecules, was found to play an important role in the spin-crossover event. The spin-transition temperature was tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…[31][32][33][34] These two features could also be associated within a unique molecular component, using lipophilic sulfonate counter-anions to drive the formation of supramolecular gels. 35 Alternatively, a series of triazole ligands bearing large lipophilic a Sorbonne Universités, UPMC Univ Paris 06, Collège de France, UMR CNRS 7574, substituents were used to form one-dimensional coordination polymers that could further assemble in a gel phase. 10,13 These works have evidenced the importance of the dimensional structure (two-or three-) in the cooperativity effect associated with the spin transition, where the temperature dependence of the high spin molar fraction strongly depends on intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] These two features could also be associated within a unique molecular component, using lipophilic sulfonate counter-anions to drive the formation of supramolecular gels. 35 Alternatively, a series of triazole ligands bearing large lipophilic a Sorbonne Universités, UPMC Univ Paris 06, Collège de France, UMR CNRS 7574, substituents were used to form one-dimensional coordination polymers that could further assemble in a gel phase. 10,13 These works have evidenced the importance of the dimensional structure (two-or three-) in the cooperativity effect associated with the spin transition, where the temperature dependence of the high spin molar fraction strongly depends on intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This included the discovery of several new examples of SCO compounds [3,[9][10][11], the explanation of different types of SCO profiles [4,12] and the modification of SCO compounds to increase cooperativity and to direct their application into materials science [13]. Scientists have developed SCO networks [14][15][16], frameworks [17][18][19], gels [20][21][22], liquid crystals [23][24][25], nanoparticles and nanocrystals [26][27][28][29], nanowires [30], thin films [31][32][33] and have also applied patterning techniques to fabricate SCO devices [34]. Among complexes displaying SCO, [Fe(salEen) 2 ] + derivatives (salEen = N-ethyl-N-(2-aminoethyl)salicylaldiminate) are known to undergo thermal SCO sensitive to unit cell contents and supramolecular packing in the crystal [35].…”
Section: Introductionmentioning
confidence: 99%
“…These systems have either been polymeric systems of the form {[Fe(4R-trz) 3 ]X 2 } n , where 4R-trz is a 1,2,4-triazole moiety with a hydrophobic substituent at N 4 of the triazole ring, 6 or discrete complexes of the form [FeL 2 (NCS) 2 ], where L represents 50 either phenanthroline or 2,2'-bipyridine groups that have been modified to contain long alkyl chains. 7 ,8 Recently, Aida et al 9 reported the preparation of gels of the form [Fe(4R-trz) 3 ](C n SO 3 ) 2 , where C n SO 3 represents the sulfonate derivative of an alkyl chain containing n carbon 55 atoms. These systems incorporate hydrophobicity both in the ligand, and in the non-coordinating counterion used (when n is large).…”
mentioning
confidence: 99%